PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA DALAM MENDUKUNG KEMAMPUAN ABAD 21 - Isna Rafianti; Nurul Anriani; Khairida Iskandar (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2018)
The abilities of the 21st century consist of critical thinking and problem solving, creativity and innovation, communication, and collaboration. To support the development of this capability, it is necessary to design a 21st century mathematics-based learning tool. Based on field observations, teachers have not been able to develop a learning tool that leads to this capability. This is due to the lack of knowledge of teachers in designing such learning. If a teacher understands and is able to design a mathematics lesson that leads to 21st century skills, then as a teacher they will be ready to apply it and, in the end 21st century skills for students will flourish. The research approach that will be used in this research is the development research with the aim of producing the product in the form of lesson plans, student worksheets and standard instruments that support the ability of the 21st century. The development model that will be used in this research is 4D development model which includes four stages: define, design, develop and disseminate. But developers only use three stages. The results show that based on the overall score that has been obtained from the testing process shows that the learning tool of mathematics is very good.